Affective Intellectuals and the Space of Catastrophe in the Americas - Sierra-Rivera, Judith (The Ohio State University Press, 2018)
Most importantly, the book shows how literature constitutes an alternative public sphere for Black people. In a society largely controlled by white supremacist actors and institutions, Black authors have conjured fiction into a space where hard questions can be asked and answered and where the work of combatting collective, racist suppression can occur without replicating oppressive hierarchies. Intimate Antagonisms uncovers a key theme in Black fiction and argues that literature itself is a vital institutional site within Black life. Through the examination of intimate conflicts in a wide array of twentieth- and twenty-first-century novels, Blake demonstrates the centrality of intraracial relations to the complexity and vision of Black social movements and liberation struggles and the power and promise of Black narrative in reshaping struggle.